CoMFA/CoMSIA and Pharmacophore Modelling as a Powerful Tools for Efficient Virtual Screening: Application to Anti-Leishmanial Betulin Derivatives - Ghemtio, Leo; Zhang, Yuezhou; Xhaard, Henri (IntechOpen, 2012)
None